Green and Energy-Saving Ecological Reconstruction Design of Existing Buildings in Cities in Severe Cold Areas. - Zhang, Huan; Yang, Tao (Journal of Environmental & Public Health, 2022)
In order to improve the overall structural stability and thermal insulation capacity of existing buildings in severe cold areas, green energy-saving ecological transformation methods of existing buildings in severe cold areas are proposed. The concrete stress analysis method of the joints in the frame is used to calculate the bearing capacity and prestress of the beam-column joints. Based on the method of parameter analysis, the calculation model of shear capacity is established. The embedded anchoring method is adopted to realize the equal strength connection of beam-column joints. Increase the unbalanced moment between reinforcement and steel plate, and improve the stability and reliability of beam-column joint fixation. The overall structural optimization method of joint shear performance is adopted to reduce the distance between lap reinforcement and steel plate, so as to realize the green energy-saving ecological transformation design of existing urban buildings in severe cold areas. The test results show that the service stress and tensile resistance of the reconstructed existing building area are higher than 60, the tensile capacity is good, and the slip of the lap reinforcement is effectively controlled. At the same time, this method improves the stability of beam-column elements and the overall thermal insulation performance of existing buildings in cities in severe cold areas. The next research will focus on the transformation of other structures.